2022
DOI: 10.3390/w14213568
|View full text |Cite
|
Sign up to set email alerts
|

Critical Evaluation of Different Passive Sampler Materials and Approaches for the Recovery of SARS-CoV-2, Faecal-Indicator Viruses and Bacteria from Wastewater

Abstract: During the COVID-19 pandemic, wastewater-based epidemiology (WBE) has proven to be an effective tool for monitoring the prevalence of SARS-CoV-2 in urban communities. However, low-cost, simple, and reliable wastewater sampling techniques are still needed to promote the widespread adoption of WBE in many countries. Since their first use for public health surveillance in the 1950s, many types of passive samplers have been proposed, however, there have been few systematic studies comparing their ability to co-cap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 90 publications
2
9
0
Order By: Relevance
“…Additional passive sampling papers are reviewed by Shakallis et al (2022) . These previous studies reinforce our choice of tampons as our passive sampling device since several of them ( Jones et al, 2022 ; Kevill et al, 2022 ; Li et al, 2022 ) concluded that tampons were better capture devices than several other alternatives, considering effective capture, cost, and convenience. Several studies that analyzed the kinetics of uptake of viral markers by various swab devices concluded that uptake begins to taper off within 4–8 h ( Hayes et al, 2022a ; Jones et al, 2022 ; Li et al, 2022 ).…”
Section: Discussionsupporting
confidence: 68%
See 3 more Smart Citations
“…Additional passive sampling papers are reviewed by Shakallis et al (2022) . These previous studies reinforce our choice of tampons as our passive sampling device since several of them ( Jones et al, 2022 ; Kevill et al, 2022 ; Li et al, 2022 ) concluded that tampons were better capture devices than several other alternatives, considering effective capture, cost, and convenience. Several studies that analyzed the kinetics of uptake of viral markers by various swab devices concluded that uptake begins to taper off within 4–8 h ( Hayes et al, 2022a ; Jones et al, 2022 ; Li et al, 2022 ).…”
Section: Discussionsupporting
confidence: 68%
“…These previous studies reinforce our choice of tampons as our passive sampling device since several of them ( Jones et al, 2022 ; Kevill et al, 2022 ; Li et al, 2022 ) concluded that tampons were better capture devices than several other alternatives, considering effective capture, cost, and convenience. Several studies that analyzed the kinetics of uptake of viral markers by various swab devices concluded that uptake begins to taper off within 4–8 h ( Hayes et al, 2022a ; Jones et al, 2022 ; Li et al, 2022 ). Three to 4 h of passive collecting seems to us to be an optimal time for gathering significant signal (as in Bivins et al (2022) ) and yet still be able to do same-day processing in time to give a rapid warning of a rise of markers of infections.…”
Section: Discussionsupporting
confidence: 68%
See 2 more Smart Citations
“…4 To our knowledge our study is the first one testing the rationality of using two membranes from the same sampling device to give reliable results. 5,7,47,48 In the current work, two electronegative membranes were tested per torpedo device to evaluate the presence of 3 different viral targets using qPCR: two viral indicators of human faecal contamination (HAdV and JCPyV) and SARS-CoV-2 (N1). A total of 15 PS, each containing 2 membranes, were collected in parallel to two 24 h-AS replicates.…”
Section: Determination Of the Number Of Membranes Needed For A Repres...mentioning
confidence: 99%